Predictive capacity of anthropometric indicators for dyslipidemia screening in children and adolescents - Teresa Maria Bianchini de Quadros; Alex Pinheiro Gordia; Rosane Carla Rosendo da Silva; Luciana Rodrigues Silva (Elsevier, 2015)
Objective: To analyze the predictive capacity of anthropometric indicators and their cut-off values for dyslipidemia screening in children and adolescents. Methods: This was a cross-sectional study involving 1139 children and adolescents, of both sexes, aged 6-18 years. Body weight, height, waist circumference, subscapular, and triceps skinfold thickness were measured. The body mass index and waist-to-height ratio were calculated. Children and adolescents exhibiting at least one of the following lipid alterations were defined as having dyslipidemia: elevated total cholesterol, low high-density lipoprotein, elevated low-density lipoprotein, and high triglyceride concentration. A receiver operating characteristic curve was constructed and the area under the curve, sensitivity, and specificity was calculated for the parameters analyzed. Results: The prevalence of dyslipidemia was 62.1%. The waist-to-height ratio, waist circumference, subscapular, body mass index, and triceps skinfold thickness, in this order, presented the largest number of significant accuracies, ranging from 0.59 to 0.78. The associations of the anthropometric indicators with dyslipidemia were stronger among adolescents than among children. Significant differences between accuracies of the anthropometric indicators were only observed by the end of adolescence; the accuracy of waist-to-height ratio was higher than that of subscapular (p = 0.048) for females, and the accuracy of waist circumference was higher than that of subscapular (p = 0.029) and body mass index (p = 0.012) for males. In general, the cut-off values of the anthropometric predictors of dyslipidemia increased with age, except for waist-to-height ratio. Sensitivity and specificity varied substantially between anthropometric indicators, ranging from 75.6 to 53.5 and from 75.0 to 50.0, respectively. Conclusions: The anthropometric indicators studied had little utility as screening tools for dyslipidemia, especially in children. Resumo: Objetivo: Analisar a capacidade preditiva dos indicadores antropométricos e os seus valores de corte para a triagem da dislipidemia em crianças e adolescentes. Métodos: Estudo transversal de 1.139 crianças e adolescentes de ambos os sexos com idade entre 6 e 18 anos. Peso corporal, estatura, circunferência da cintura (CC) e prega cutânea subescapular (PCSE) e prega cutânea tricipital (PCT) foram medidos. O índice de massa corporal (IMC) e relação cintura-estatura (RCE) foram calculados. As crianças e adolescentes que tinham pelo menos uma das seguintes alterações lipídicas foram definidos como tendo dislipidemia: elevados níveis de colesterol total, HDL-C baixo, LDL-C elevado, e concentração elevada de triglicérides. Uma curva ROC (Receiver Operating Characteristics) foi construída e a área sob a curva, a sensibilidade e especificidade foram calculadas para os parâmetros analisados. Resultados: A prevalência de dislipidemia foi de 62,1%. RCE, CC, PCSE, IMC e PCT, nesta ordem, apresentaram o maior número de precisões significantes, variando de 0,59-0,78. As associações dos indicadores antropométricos com dislipidemia foram mais fortes nos adolescentes do que nas crianças. Diferenças significantes entre precisões dos indicadores antropométricos só foram observadas no final da adolescência, sendo a precisão da RCE maior do que a da PCSE (p = 0,048) para meninas e a precisão de CC sendo maior do que a PCSE (p = 0,029) e IMC (p = 0,012) para os meninos. Em geral, os valores de corte dos preditores antropométricos de dislipidemia aumentaram com a idade, exceto para RCE. Sensibilidade e especificidade variaram substancialmente entre os indicadores antropométricos, variando de 75,6-53,5 e 75,0-50,0, respectivamente. Conclusões: Os indicadores antropométricos estudados mostraram pouca utilidade como ferramentas de rastreamento para dislipidemia, especialmente em crianças. Keywords: Dyslipidemia, Body mass index, Abdominal circumference, Skinfold thickness, Child, Adolescent, Palavras-chave: Dislipidemia, Índice de massa corporal, Circunferência abdominal, Dobras cutâneas, Criança, Adolescente